2015
DOI: 10.1016/j.clinbiochem.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of practices for improving the diagnostic accuracy of Non ST Elevation Myocardial Infarction in the Emergency Department: A Laboratory Medicine Best Practices™ systematic review

Abstract: Objectives This article presents evidence from a systematic review of the effectiveness of four practices (assay selection, decision point cardiac troponin (cTn) threshold selection, serial testing, and point of care testing) for improving the diagnostic accuracy for Non-ST-Segment Elevation Myocardial Infarction (NSTEMI) in the Emergency Department. Design and Methods The CDC-funded Laboratory Medicine Best Practices (LMBP™) Initiative systematic review A6 Method for Laboratory Best Practices was used. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Adoption of the 99th percentile as a single cut point as recommended as a Laboratory Medicine Best Practice6 holds significant diagnostic and prognostic implications in the evaluation of AMI, given that it increases the diagnosis of AMI and identifies patients at greater risk for both readmission and recurrent AMI in comparison with higher cut points 4, 5. We found wide variation in the choice of diagnostic cut points by institution, with cumulatively less than half (49%) using the 99th percentile, although use did increase over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoption of the 99th percentile as a single cut point as recommended as a Laboratory Medicine Best Practice6 holds significant diagnostic and prognostic implications in the evaluation of AMI, given that it increases the diagnosis of AMI and identifies patients at greater risk for both readmission and recurrent AMI in comparison with higher cut points 4, 5. We found wide variation in the choice of diagnostic cut points by institution, with cumulatively less than half (49%) using the 99th percentile, although use did increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, use of the 99th percentile as the cut‐off value increases the frequency of AMI diagnosis, has been associated with improved outcomes, and is championed as a Laboratory Medicine Best Practice 4, 5, 6. Guidelines were updated in 2012, shortening the marker sampling interval to 3 to 6 hours, reflecting the improved cTn assay sensitivity 3.…”
mentioning
confidence: 99%
“…(7). We hypothesized that considerable variability existed in utilization and reporting of cTn across institutions and that there were likely additional differences in use of cTn between adult and pediatric hospitals.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A recent systematic review demonstrated evidence supporting serial cTn testing and analysis of acute changes to increase specificity and NPV, with a modest decrease in positive predictive value for diagnosis of NSTEMI(7). The timing protocol and definition for significance of change varied among the evidence base although it is clear that delta analysis should never be used for sensitivity or PPV.…”
mentioning
confidence: 96%
“…Currently, expert consensus and evidence-based documents strongly advocate the 99th percentile as the appropriate upper reference limit for cTn concentrations [12,30]. Clinical outcome studies solidified these recommendations; several retrospective and prospective studies have indicated that, in the context of acute coronary syndromes, a cTn concentration above this threshold portended worse outcomes.…”
Section: Selection Of the Clinical Decision Limit To Be Used By Labormentioning
confidence: 99%